Structures and Functions of Lexical Bundles in Findings and Discussion Sections of Graduate Students’ Thesis - Wachidah, Wahyu Dyah Nur Anis; Fitriati, Sri Wuli; Widhiyanto, Widhiyanto (English Education Journal, 2020)
Lexical bundles is a combination of words which consists of three or even more words that frequently occur together in particular registers. It is seen as an important aspect that should be mastered in order to create a qualified text. This study aims at analyzing the lexical bundles used in findings and discussion sections of graduate students’ thesis in terms of structures, functions, and the role of lexical bundles in forming coherence of the students’ texts. This study employs qualitative approach. The data are taken from 10 Chapter IV, Findings and Discussion of graduate students’ thesis. In the process of analysis, the researcher uses three instruments in the form of tables to collect and analyze the lexical bundles manually based on the structures of lexical bundles proposed by Biber, et. al. (1999), and the functions of lexical bundles proposed by Hyland (2008) framework. There are 74 lexical bundles found in the students’ texts. The findings reveals that first, the lexical bundles found in the students’ texts make use of all the twelve structural forms and the most dominantly used is structure type 4 other prepositional phrase (fragment); second, the lexical bundles found in the students’ texts serve all of the three functional types and the most dominantly used is text-oriented function and third, the lexical bundles found in the students’ texts have an important role in forming coherence of the texts. It indicates that the lexical bundles make use of two coherence items such as reference and transition signals.